An analysis of distribution transformer failure using the statistical package for the social sciences (SPSS) software - Mago Ramos, María Gabriela; Valles Defendine, Luis; Olaya Florez, Jhon Jairo (Ingeniería e Investigación, 2012)
A methodology was developed for analysing faults in distribution transformers using the statistical package for social sciences (SPSS); it consisted of organising and creating of database regarding failed equipment, incorporating such data into the processing programme and converting all the information into numerical variables to be processed, thereby obtaining descriptive statistics and enabling factor and discriminant analysis. The research was based on information provided by companies in areas served by Corpoelec (Valencia, Venezuela) and Codensa (Bogotá, Colombia).